A magyar nemzeti kisebbség helyzetének néhány aspektusa az első Csehszlovák Köztársaságban : 1918-1938 - Tóth, Andrej (Közép-Európai Közlemények, 2012)
The multinational Austro-Hungarian Monarchy was replaced by successor states after World War I. But in the end, those states did not become national states, as had been originally expected, but nationally mixed states as well. The Czechoslovak Republic had one of the most varied national compositions of population among the established successor states. The second most numerous national minority, after the German national minority numbering more than three million inhabitants, consisted of about 750 000 Hungarians. The political representation of the Hungarian minority, opposing the government during the whole period of duration of the First Czechoslovak Republic, criticized permanently the unequal status of the Hungarian minority against the majority Czechoslovak nation. They criticized for example the unequal conditions for political representation of the Hungarian population in the National Assembly, caused by the unfavourable borders of electoral districts in the regions with Hungarian majority where the number of inhabitants falling on one deputy and senator mandate was markedly higher than in the electoral districts in the historical countries. The political representatives of the Hungarian-speaking population criticized also the Language Act from 1920 and the respective implementation provision from 1926. They called the conditions for use of minority language in contact with authorities, standardized in them, insufficient and demanded their extension. The Czechoslovak Hungarian minority politicians subjected also the area of education to strong criticism. The criticism of the status of the minority Hungarians in the First Czechoslovak Republic, expressed by the political representation of the Hungarian minority, was very extensive and it concerned a great number of areas of the political, social and cultural life of the Hungarian minority. But in spite of all errors that the Czechoslovak state of that time had, it must be stated that the First Czechoslovak Republic was the undoubtedly most democratic state in the Central-Eastern European space. With regard to the study of the legal status of the national minorities in the First Czechoslovak Republic, it is necessary to emphasize the basic characteristic of the legal system or of the legal state limits of the interwar Czechoslovak state that determined the dominant positions of individual civil rights that, via facti, took precedence over the collective rights.